Epidural Baclofen for the Management of Postoperative Pain in Children With Cerebral Palsy. Issue 6 (September 2015) - Nemeth, Blaise A.; Montero, Robert J.; Halanski, Matthew A.; Noonan, Kenneth J.
Abstract : Introduction: Children with cerebral palsy undergoing soft tissue and bony procedures often experience pain and spasticity postoperatively. Differentiation of pain from spasticity complicates management, so controlling spasticity with a continuous infusion of baclofen, an antispasmodic, through an already present indwelling epidural catheter holds interest. Methods: A retrospective chart review was performed of patients with cerebral palsy undergoing single event, multilevel lower extremity surgery at a single institution who received epidural analgesia with or without continuous baclofen infusion. Primary outcomes included need for supplemental narcotic analgesics and benzodiazepines postoperatively. Duration of hospitalization, pain scores, and complications were also evaluated. Results: Forty-four patients were identified, ranging in age from 3 to 17 years, 19 of whom received epidural baclofen. No differences were found in use of supplemental narcotic analgesia, benzodiazepines, or duration of hospitalization. Differences in pain scores were not statistically significant (0.82±0.95 for baclofen vs. 1.48±0.99 for controls) ( P =0.391). Mean arterial pressure was lower in patients receiving baclofen ( P =0.004). No potential side effects attributable to baclofen were noted. Conclusions: Continuous epidural baclofen infusion seems unlikely to alter the pain-spasm cycle experienced by patients with cerebral palsy following orthopaedic surgery to a clinically significant degree. More effective, and cost-effective, measures at assessing and controlling pain and muscle spasm should be explored to benefit cerebral palsy patients postoperatively. Level of Evidence: Level III—therapeutic study.